EFFECT OF SUPPLY CHAIN MANAGEMENT PRACTICES ON THE PERFORMANCE OF DANGOTE CEMENT COMPANY OBAJANA, KOGI STATE (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2025)
Dangote Cement Manufacturing Company, Obajana, struggles to optimize its supply chain for cost and operational efficiency due to infrastructural deficits, market volatility, and unreliable supplier performance. This study explored the effect of supply chain management practices on the company’s performance. The combination of descriptive and survey research designs was used and the main research instrument was structured questionnaire. Data were collected from employees of Dangote Cement Plc at Obajana, Using Taro Yamane formula, it took a sample of 412 employees from the population of 2,428 employees. Stratified and simple random sampling techniques were applied within each stratum, and a sample size of 347 was determined, with an additional 20% margin of safety. The data were analyzed using inferential statistics and regression analysis, with a 5% level of significance to test the hypotheses aligned with the study's objectives. The findings revealed that strategic suppliers’ partnership and internal lean practices had significant positive effects on the performance of Dangote cement manufacturing company. More so, while these two factors contribute significantly to the performance of Dangote Cement Plc, internal lean practices showed the most pronounced impact, reinforcing the importance of continuous improvement and waste reduction strategies. The study concluded that supply chain management practices had positive effect on the performance of Dangote cement manufacturing company Obajana, despite the complexities and dynamism from business contexts. Based on the findings, the study recommends that Dangote Cement should enhance collaboration and communication with suppliers and distributors through joint planning and regular updates and adopt lean tools like value stream mapping, 5S, and Kaizen to boost efficiency.